A novel intelligently integrated MOF-based ratio fluorescence sensor for ultra-sensitive monitoring of TC in water and food samples. (30th March 2023) - Chen, Xiangzhen; Xu, Jun; Li, Yongxin; Zhang, Lina; Bi, Ning; Gou, Jian; Zhu, Taofeng; Jia, Lei
Highlights: A novel multicolor probe based on Zif-8 and rare earth. Realization of TC visual detection with high recognition. Ultrafast POCT detection of TC in various water and food samples. Combined application of gelled detection device and intelligent APP. Abstract: In this work, a high-precision visual and point-of-care testing (POCT) ratiometric fluorescent nanosensor for TC was constructed by embedding fluorescein (FL) into l -histidine modified ZIF-8 (LZIF-8) and chelating with rare earth citrate complex. Upon exposure to TC, the coordination and energy transfer between Eu 3+ and TC make Eu 3+ sensitized emission characteristic red fluorescence, while without prejudice to the emission peak intensity of FL. This ratiometric fluorescent probe with stable reference signal had the characteristics of high sensitivity (ultralow LOD = 5.99 nM) and selectivity and fast response kinetics (within 20 s). The high-bright fluorescence emission was beneficial to human eye recognition and it can realize semi-quantitative detection of TC in eggs, meeting the requirements of household use. In addition, the color can be read and analyzed quickly with the help of smart phone color analysis APP, and the semi-quantitative concentration of TC can be determined more conveniently.